Perancangan on line public access catalog (OPAC) system berbasis intranet - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Up to now, the catalog information service of field research report (LKP) and thesis (TGA) at the Department of Physical Engineering, Faculty of Engineering, Gadjah Mada University is managed manually. Considering the fact that the library trend in the future is a network based library, suitable electronic library development is very important. Therefore, design of the OPAC system (Online Public Access Catalog) is directed to computerize and to make the catalog information could be accessed by all computers in local area network (OPAC based on LAN). The OPAC based on LAN is designed by using Microsoft Visual Basic Program, 6.0 Enterprise Edition. By using OPAC system, students, lecturers and others users can find any catalog information about LKP and TGA on their computer (work station) that connected to the local area network quickly. Keywords: system berbasis intranet, OPAC